Political ideology, cooperation, and national parochialism across 42 nations - Angelo Romano; Matthias Sutter; James Hou-fu Liu; Daniel Balliet (Max Planck Institute for Research on Collective Goods, 2020)
Political ideology has been hypothesized to be associated with cooperation and national parochialism (i.e., greater cooperation with members of one's nation), with liberals thought to have more cooperation with strangers and less national parochialism, compared to conservatives. However, previous findings are limited to few - and predominantly western - nations. Here, we present a large-scale cross-societal experiment that can test hypotheses on the relation between political ideology, cooperation, and national parochialism around the globe. To do so, we recruited 18,411 participants from 42 nations. Participants made decisions in a prisoner's dilemma game, and we manipulated the nationality of their interaction partner (national ingroup member, national outgroup member, or unidentified stranger). We found that liberals, compared to conservatives, displayed slightly greater cooperation, trust in others, and greater identification with the world as a whole. Conservatives, however, identified more strongly with their own nation and displayed slightly greater national parochialism in cooperation. Importantly, the association between political ideology and behavior was significant in nations characterized by higher wealth, stronger rule of law, and better government effectiveness. We discuss the implications of these findings for understanding the association between political ideology and cooperation.
Keywords: 330; Cooperation; political ideology; culture; parochial altruism